High-performance hydrogen evolution electrocatalysis using proton-intercalated TiO2 nanotube arrays as interactive supports for Ir nanoparticles. Issue 43 (27th October 2020) - Lačnjevac, Uroš; Vasilić, Rastko; Dobrota, Ana; Đurđić, Slađana; Tomanec, Ondřej; Zbořil, Radek; Mohajernia, Shiva; Nguyen, Nhat Truong; Skorodumova, Natalia; Manojlović, Dragan; Elezović, Nevenka; Pašti, Igor; et al.
Abstract : Surface-disordered, protonated TiO2 nanotube array substrates induce spontaneous deposition of metallic Ir nanoparticles and actively promote their electrocatalytic behavior for achieving remarkable hydrogen evolution activity in acidic media. Abstract : Developing ultraefficient electrocatalytic materials for the hydrogen evolution reaction (HER) with low content of expensive platinum group metals (PGMs) via low-energy-input procedures is the key to the successful commercialization of green water electrolysis technologies for sustainable production of high-purity hydrogen. In this study, we report a facile room-temperature synthesis of ultrafine metallic Ir nanoparticles on conductive, proton-intercalated TiO2 nanotube (H-TNT) arrays via galvanic displacement. A series of experiments demonstrate that a controlled transformation of the H-TNT surface microstructure from neat open-top tubes to disordered nanostripe bundles ("nanograss") is highly beneficial for providing an abundance of exposed Ir active sites. Consequently, for nanograss-engineered composites, outstanding HER activity metrics are achieved even at very low Ir(iii ) precursor concentrations. An optimum Ir@TNT cathode loaded with 5.7 μgIr cm −2 exhibits an overpotential of −63 mV at −100 mA cm −2 and a mass activity of 34 A mgIr −1 at −80 mV under acidic conditions, along with excellent catalytic durability and structural integrity. Density functional theory (DFT) simulations reveal that the hydrogen-rich TiO2 surface not only stabilizes the deposited Ir and weakens its H binding strength to a moderate intensity, but also actively takes part in the HER mechanism by refreshing the Ir catalytic sites near the Ir|H–TiO2 interface, thus substantially promoting H2 generation. The comprehensive characterization combined with theory provides an in-depth understanding of the electrocatalytic behavior of H-TNT supported PGM nanoparticles and demonstrates their high potential as competitive electrocatalyst systems for the HER.